Asymmetric aminohydroxylation route to cis-2,6-disubstituted piperidine-3-ol: application to the synthesis of (-)-deoxocassine - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron, 2006)
A highly efficient, flexible, and convergent route to cis-2,3,6-trisubstituted piperidines has been developed employing the Sharpless asymmetric aminohydroxylation and stereoselective reductive amination by catalytic hydrogenation as the key steps. Its usage is illustrated by the short synthesis of the piperidine-3-ol alkaloid, (-)-deoxocassine. (c) 2006 Elsevier Ltd. All rights reserved.